Towards a Shariah-Compliant Social and Reproductive Health Education in Malaysia: Protecting the Muslim Family from Social Deviations - Binti Masnan, Suryani; Bin Yussuf, Ahmad; Binti Salleh, Siti Fatimah (El-Usrah: Jurnal Hukum Keluarga, 2025)
This study addresses the urgent need for a Shariah-Compliant Index for Social and Reproductive Health Education (SCI-SRHE) in Malaysia, given the growing misalignment between current SRHE modules and Islamic principles. The core research questions aim to explore to what extent existing SRHE modules, particularly the ACE and PEERS modules, align with the objectives of Maqasid al-Shariah, and how a Shariah-based framework can enhance content compliance. Employing a qualitative content analysis, this research critically examines these modules against Islamic sources, including Qur’anic texts, Prophetic traditions, classical scholarship, and national fatwa rulings. The study further conceptualizes SCI-SRHE by integrating Maqasid al-Shariah with Fiqh al-Awlawiyyat to guide content prioritization. The findings reveal that while PEERS emphasizes abstinence and moral conduct, it often leaves key values implicit and open to varying interpretations. In contrast, ACE reflects liberal values, including promotion of safe sex, gender fluidity, and contraceptive use without marital distinction, which conflict with Islamic teachings. The study proposes SCI-SRHE as an evaluative tool to systematically realign SRHE content with Shariah objectives, offering a principled framework for policymakers, educators, and religious authorities. This framework aims not only to protect Muslim youth from moral confusion but also to uphold the integrity of the family institution. The proposed index has potential as a model for Muslim-majority countries seeking to harmonize sexuality education with religious values